2013
DOI: 10.2147/dmso.s36024
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-based wound dressings for the treatment of diabetes-related foot ulcers: a systematic review

Abstract: BackgroundDiabetic foot ulcers are a major source of morbidity, limb loss, and mortality. A prolonged inflammatory response, extracellular matrix degradation irregularities, and increased bacteria presence have all been hypothesized as major contributing factors in the delayed healing of diabetic wounds. Collagen components such as fibroblast and keratinocytes are fundamental to the process of wound healing and skin formation. Wound dressings that contain collagen products create a biological scaffold matrix t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 66 publications
3
51
1
2
Order By: Relevance
“…It is a secreted serine protease that converts the proenzyme plasminogen to plasmin and plays a critical role in cell migration and tissue remodeling. Keratinocytes use plasmin activated by plasminogen activators for paving their way through phase of the wound-healing process (47), and its inhibition, as seen in our study and also reported by others (34,48), is one of the main reason for the delay in wound closure. Ctgf and transforming growth factor b1 (Tgfb1) were significantly upregulated.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It is a secreted serine protease that converts the proenzyme plasminogen to plasmin and plays a critical role in cell migration and tissue remodeling. Keratinocytes use plasmin activated by plasminogen activators for paving their way through phase of the wound-healing process (47), and its inhibition, as seen in our study and also reported by others (34,48), is one of the main reason for the delay in wound closure. Ctgf and transforming growth factor b1 (Tgfb1) were significantly upregulated.…”
Section: Resultssupporting
confidence: 86%
“…Dicer knockout (KO) mice show follicular epithelial progenitors evaginating into the epidermal surface instead of into the dermis (40,41). Notch and sonic hedgehog and epithelial are thought to be effective for delayed wound closure (34). Wnt5a and Itgav, components of the Wnt signaling and Integrin signaling pathways, respectively, also depicted multiple interactions with the miRNA predicted regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Both are contraindicated in wounds with signs of infection. In addition, they are recommended for limbs with good blood supply, and in some cases several applications of the scaffold are required (Veves et al, 2001;Marston et al, 2003;O'Loughlin et al, 2010;Holmes et al, 2013). Other therapies, such as hyperbaric oxygen and negative pressure, have emerged also as potential non-surgical alternatives for treating DFU; however, clinical evidence does not fully support their use (Londahl et al, 2010;Dumville et al, 2013;Ma et al, 2013;Rhee et al, 2014;Cychosz et al, 2015).…”
Section: Diabetic Foot and Tissue Engineeringmentioning
confidence: 99%
“…In the early 1970's, John F. Burke and Ioannas Yannas developed a bio-compatible collagen matrix to improve wound healing. It is commonly used in the management of burns, [6] diabetic foot ulcer, [7,8] toxic epidermal necrolysis, [9] chronic wounds, etc. [10][11][12] This versatile material also finds its application in the field of plastic surgery, oral and maxillofacial surgery and dentistry for various purposes e.g.…”
Section: Collagen As a Biomaterials In Plastic And Reconstructive Surgerymentioning
confidence: 99%